Social relationships, mental health and wellbeing in physical disability: a systematic review - Hannah Tough; Johannes Siegrist; Christine Fekete (BMC, 2017)
Abstract Background Research has consistently found that favourable exchange with one's proximal social environment has positive effects on both mental health and wellbeing. Adults with physical disabilities may have fewer opportunities of favourable exchange, and therefore the effects on mental health and wellbeing may be less advantageous. The aim of this study is to systematically review quantitative studies exploring associations of social relationships with mental health and wellbeing in persons with physical disabilities. Methods The databases PubMed, PsycINFO and Scopus were searched for relevant studies published between 1995 and 2016. Data was extracted on study and participants' characteristics, independent and dependent variables, used measures and effects sizes of associations between social relationships and mental health or wellbeing. A narrative review was performed to synthesize findings along the constructs social support, social networks, negative social interactions, family functioning and relationship quality. Results Of the 63 included studies, 47 were cross-sectional and 16 longitudinal. Most studies included a measure of social support (n = 58), while other concepts were less often studied (social networks n = 6; negative social interaction n = 3; family functioning n = 2; relationship quality n = 1). Over half of studies included depression as outcome (n = 33), followed by wellbeing (n = 14), composite mental health measures (n = 10), anxiety (n = 8), psychological distress (n = 7), posttraumatic stress disorder (n = 3), and hopelessness (n = 1). Although trends for associations of social support with mental health and wellbeing were consistent, around a quarter of studies failed to report significant associations. Social networks were related to depression, but not to other mental health or wellbeing measures. Family functioning, negative social interactions and relationship quality showed consistent associations with mental health and wellbeing, however, only few studies were available. Conclusions This review indicates that social relationships play an important role in mental health and wellbeing in persons with disabilities, although findings are less consistent than in general populations and strength of associations vary between constructs. Integrating persons with disabilities into social networks seems not sufficient and rehabilitation professionals together with affected persons and their peers should ensure that high quality relationships and tailored support are available.